El sentido de la tierra. Materialidad, vegetalidad y subjetividad en el texto temprano de Jacques Derrida - Sorin, Ana (2019)
“The Sense of the Soil. Materiality, Vegetality and Subjectivity in Jacques Derrida’s Early Text”. Derrida often says that the question of other living beings, i.e., of the other than the human, has always concerned his writing, even when it was not an explicit theme of his formulations. This paper aims to address this assertion as an occasion to question whether such concern was similarly treated in all cases, or if perhaps the different topics, interlocutors and, in short, textures that Derridian writing goes through, do not bring relevant philosophical impacts for the approach of such problem. To do so, The voice and the phenomenon (1967) will be studied through the main thesis of plantism as developed by M. Marder and J.T. Nealon, recognizing nevertheless that plants do not usually constitute the non-human living beings Derrida refers to. In this sense, and without pretending to “reveal what Derrida really meant”, this research seeks to examine a series of tools that we find particularly interesting to approach subjectivity from a postmetaphysical perspective.